An Agro-ecological Zoning Model Highlighting Potential Growing Areas for Medicinal Plants in Punjab - Singh, Preet Amol; Sood, Anil; Baldi, Ashish (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The Ministry of AYUSH, Government of India has decided to emerge cultivation of medicinal plants as an attractive farming option due to a sharp increase in demand for medicinal plants. Punjab produces approximately twenty and nine percent of India’s wheat and rice, respectively. At present, less than 1% of the state’s land is under Medicinal and Aromatic Plant (MAP) cultivation. Agro-ecological zoning for potential medicinal plants is one of the major constraints faced by the farmers. The present study is aimed to determine the land potential for selected medicinal plants such as Asparagus racemosus Willd. and Rauvolfia serpentina (L.) Benth. ex Kurz. in Punjab. Materials and Methods: Agro-ecological aptitudes for the plants were defined by analysing the edaphic and climatological data of the past years. Base maps of rainfall, temperature, benchmark soil were prepared, defined and superimposed using Arc. GIS 10.3 to highlight optimally suitable, suitable and lesser suitable zones for selected medicinal plants. Results and Discussion: Asparagus racemosus Willd. was: Optimally suitable to zones-II, III; Suitable to I; Lesser suitable to zone IV and V. Similarly, Rauvolfia serpentina (L.) Benth. ex Kurz, was: Optimally suitable to zone I; Suitable to II and III; Lesser suitable to IV and V. Conclusion: This agro-ecological zoning model can act as a baseline study for other medicinal plants with same or different bioclimatic indices and can be used in any part of the world for determining potential growing areas for new crops.
Keywords: Agro-climatic zoning; Asparagus racemosus Willd.; Geographical Information System; Rauvolfia serpentina (L.) Benth. ex Kurz.